HOW MANY CATEGORIES IN A CLASSIFICATION OF PSYCHIATRIC DISORDERS DO WE NEED? - Sartorius, Norman; Maric, Nadja P (Medicinski podmladak, 2017)
Communication among physicians requires a commonly accepted classification of diseases, which make it possible for them to undertake action that might prevent or control diseases. The psychiatric classifications, with over 300 different psychiatric disorders listed, are providing clinicians throughout the world with a free and accessible classification system that can be used with relative ease by mental health clinicians and scientists. Such a classification will however neither be used nor useful to other stakeholders, for example judges, policemen, family members of patients, public health authorities, etc., who deal with the same diseases but from a different perspectives. All of them will develop their classifications of diseases in harmony with the actions which they will have to take. This paper will attempt to make it clear that classifications – of objects, of concepts and of all other items with which we have to deal – will depend on their users. Understanding what classifications and diagnostic terms are used by others who see mentally ill people will enable physicians to communicate with them and to create alliances which will make it possible to provide adequate help to those who are ill, their families, general population and all these who could influence the government to search for the best ways of implementing health care policies.